723 Sleep Apnea Care During the COVID-19 Pandemic: Perspectives on the Transition to Telemedicine from Clinicians and Patients. (3rd May 2021) - Bertisch, Suzanne; Bakker, Jessie; Hanes, Sherry; Dos Santos, Carolina; Bergrestresser, Sloan; Siengsukon, Catherine; Barwick, Melanie; Redline, Susan; Revette, Anna
Abstract: Introduction: Covid-19-related public health control measures have necessitated a rapid transition in healthcare delivery. We qualitatively explored clinicians' and patients' experiences of the pandemic's impact on the delivery and receipt of obstructive sleep apnea (OSA) care. Methods: Between September and December 2020, we conducted ten 90-minute virtual focus groups with sleep clinicians (n=19) and English and Spanish-speaking patients with OSA (n= 30) recruited through an urban academic sleep clinic, national organizations, social media, and snowball sampling. An interdisciplinary team conducted a rapid qualitative analysis that included prefigured and emergent domains. The team developed a comprehensive analytic matrix, identifying key themes within and between groups and triangulating them across participant types. Results: Clinicians and patients across all groups confirmed a rapid shift to the adoption of telemedicine. Clinicians reported telemedicine enhanced evaluations by enabling direct observation of the home environment, providing opportunities to guide patients on medical equipment used in the home, and cultivating meaningful social connections for patients. Perceived benefits varied across patient subgroups (age, language, technological self-efficacy). The majority of clinicians reported that telemedicine's initial uptake resulted in delays in care and revenue loss, but sustained use was thought to be feasible over time. Patients reported delays in care related to the pandemic's disruption on healthcare and their personal safety concerns. Additionally, telemedicine's adoption directly altered other elements of care, including the delivery of patient education materials and loss of tacit information gained during the in-person visit. All groups reported adequate mask fitting as a central challenge for patients using positive airway pressure therapy. Spanish-speaking patients noted concerns of increased difficulty accessing care and navigating the OSA care system due to limited English proficiency, in addition to the limited availability of OSA resources in Spanish. Conclusion: During the Covid-19 pandemic, the rapid adoption of telemedicine largely facilitated OSA care but altered patient-clinician interactions, delivery of patient education materials, and mask fitting success. Given that telemedicine will likely be sustained post-pandemic, there are needs for targeted efforts aimed at addressing disparities in telemedicine, enhancing practitioner telepresence and education, and new approaches for mask fitting to ensure successful OSA care. Support (if any): Patient-Centered Outcomes Research Institute EADI-16493